2020
DOI: 10.1037/ort0000418
|View full text |Cite
|
Sign up to set email alerts
|

The influence of flood exposure and subsequent stressors on youth social-emotional health.

Abstract: Most disaster mental health research focuses on the relationship between disaster exposure and distress, often neglecting its influence on social-emotional health, despite implications for resilience and well-being after the disaster. Following multiple floods in Texas, a sample of 486 youth aged 10 -19 years old (M ϭ 13.74 years, SD ϭ 2.57; 52.9% male) completed measures of disaster exposure, life stressors since the disaster, and social-emotional health. Using mixture regression modeling, we examined differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…We combined the parent and child life stressors reported, following the same procedures as for flood exposure, to create a total family life stressors score. Predictive validity is supported through the negative relations of life stressors since the disaster to various aspects of social-emotional health among the children (Felix et al, 2020).…”
Section: Inventory Of Life Stressors (Ils)mentioning
confidence: 99%
“…We combined the parent and child life stressors reported, following the same procedures as for flood exposure, to create a total family life stressors score. Predictive validity is supported through the negative relations of life stressors since the disaster to various aspects of social-emotional health among the children (Felix et al, 2020).…”
Section: Inventory Of Life Stressors (Ils)mentioning
confidence: 99%
“… Makwana (2019) indicated that the psychological effects of a disaster were more severe among children, women, and the dependent elderly population. Furthermore, research showed that youth experiencing high levels of exposure to such disasters had the highest mean levels of life stressors ( Felix et al, 2020 ). Jermacane et al (2018) found that anxiety and depression among survivors of widespread flooding in the United Kingdom had a prevalence of over 10% 2 years post-disaster.…”
Section: Introductionmentioning
confidence: 99%
“…Many adolescents and their parents were trapped in their homes, and some parents volunteered to help with relief efforts. Flooding causes severe stress which continues long after the waters recede ( Felix et al, 2020 ). This prolonged stress can induce behavioral problems in children, lead to grief and economic difficulties for families, increase substance use and misuse, exacerbate existing problems, and negatively impact mental health ( Stanke et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%